Chemical profile and antimicrobial potential of essential oils of Cymbopogon citratus (DC.) Stapf, Ocimum basilicum Linn and Aniba rosaeodora Ducke - Everton, Gustavo Oliveira; Santos Júnior, Paulo Sérgio; Araújo, Rebecca Jemima Pereira; Ferreira, Aline Medeiro; Gomes, Paulo Roberto Barros; Rosa, Paulo Victor Serra; Pereira, Ana Patricia Matos; Mouchrek Filho, Victor Elias (Scientia Plena, 2020)
The study evaluated the chemical profile, antimicrobial activity and toxicity of essential oils (EOs) of C. citratus, O. basilicum and A. rosaeodora. The EOs were extracted by hydrodistillation, the chemical profile was determined using the physicochemical parameters and the chemical composition was obtained by gas chromatography coupled to mass spectrometry (GC-MS). The toxicity assay followed the Artemia salina Leach bioassay. To perform the antimicrobial activity, the Disc Diffusion technique and the Mueller Hinton Broth Dilution (MH) technique were used. The physicochemical parameters of the EOs showed satisfactory results. The major chemical composition of the EO of A. rosaeodora presented linalool (93.60%), the EO of C. citratus exhibited geranial (43.96%) and EO of O. basilicum found methyl chavicol. All EOs in this study had LC50 between 582 mg L-1 and 282 mg L-1. The antimicrobial activity of EO C. citratus demonstrated inhibition halos for S. aureus of 25 mm and 25 mm for E. coli, EO of O. basilicum exhibited inhibition halo of 18 mm for E.coli and 20 mm for S. aureus and EO of A. rosaeodora presented 11 mm for E. coli and 15 for S. aureus. As the values of MIC and MBC found, the EO of O. basilicum presented a more effective inhibitory action against S. aureus. It was concluded that the observed biological potentials encourage the application potentials in the efficiency of the control of pathogenic microorganisms.